Ebf Activates Expression of a Cholinergic Locus in a Multipolar Motor Ganglion Interneuron Subtype in Ciona - Popsuj, Sydney; Stolfi, Alberto (Frontiers in Neuroscience, 2021)
Conserved transcription factors termed “terminal selectors” regulate neuronal sub-type specification and differentiation through combinatorial transcriptional regulation of terminal differentiation genes. The unique combinations of terminal differentiation gene products in turn contribute to the functional identities of each neuron. One well-characterized terminal selector is COE (Collier/Olf/Ebf), which has been shown to activate cholinergic gene batteries in C. elegans motor neurons. However, its functions in other metazoans, particularly chordates, is less clear. Here we show that the sole COE ortholog in the non-vertebrate chordate Ciona robusta, Ebf, controls the expression of the cholinergic locus VAChT/ChAT in a single dorsal interneuron of the larval Motor Ganglion, which is presumed to be homologous to the vertebrate spinal cord. We propose that, while the function of Ebf as a regulator of cholinergic neuron identity conserved across bilaterians, its exact role may have diverged in different cholinergic neuron subtypes (e.g. interneurons vs. motor neurons) in chordate-specific motor circuits.